Burst failure of layered composite pipe - Ho, Kuan Lian (2016)
Composite pressure vessels exhibit many advantages such as high strength, lightweight and excellent resistance to fatigue and corrosion. This makes them very popular for usage in various different industries such as aerospace, chemical engineering, and the transport of oil and gas. However, these pressure vessels experience very high internal pressures during their operation. As a result, the burst pressure analysis of them becomes vital for safety purposes.